Inflammatory myopathy following coronavirus disease 2019 vaccination: A systematic review - Ding, Yukang; Ge, Yongpeng (Frontiers in Public Health, 2022)
Introduction Reports of unexpected side effects have accompanied the vaccination of larger proportions of the population against coronavirus disease 2019 (COVID-19), including a few cases of inflammatory myopathy (IM). In a bid to improve understanding of the clinical course of vaccine complications, a systematic review of reported cases of IM following COVID-19 vaccination has been conducted. Methods The PRISMA guideline 2020 was followed. Two independent investigators systematically searched PubMed and Embase to identify relevant studies published up to July 2022, using the following keywords: COVID-19 Vaccine, inflammatory myositis. The Joanna Briggs Institute critical appraisal tools were used for the risk of bias. Results A total of 24 articles presenting clinical features of 37 patients with IM following COVID-19 vaccine were identified. Female patients composed 59.5% of cases and 82.4% had been vaccinated with BNT162b2 or ChAdOx1. Onset of symptoms occurred within 2 weeks of the first or second vaccine dose in 29 (85.3%) patients and included muscular weakness in 54.1% and skin rash in 71.4% of patients. Myositis specific autoantibodies (MSAs) and myositis associated autoantibodies (MAAs) were reported in 28 patients. Specific clinical subtypes of myositis, reported in 27 patients, included 22 (81.5%) cases of dermatomyositis (DM) and 3 (11.1%) cases of immune-mediated necrotizing myopathy (IMNM). Following treatment, 32 (86.5%) patients showed improvement on follow-up. Conclusion COVID-19 vaccine may induce various clinical myositis subtypes and related antibodies. Muscular weakness was the most common presenting symptom. Clinicians should be aware of this unexpected adverse event following COVID-19 vaccination and arrange for appropriate management. Systematic review registration INPLASY https://inplasy.com/inplasy-2022-9-0084/ [INPLASY202290084].